If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y + 14 = 180 Reorder the terms: 14 + 2x + y = 180 Solving 14 + 2x + y = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + 2x + -14 + y = 180 + -14 Reorder the terms: 14 + -14 + 2x + y = 180 + -14 Combine like terms: 14 + -14 = 0 0 + 2x + y = 180 + -14 2x + y = 180 + -14 Combine like terms: 180 + -14 = 166 2x + y = 166 Add '-1y' to each side of the equation. 2x + y + -1y = 166 + -1y Combine like terms: y + -1y = 0 2x + 0 = 166 + -1y 2x = 166 + -1y Divide each side by '2'. x = 83 + -0.5y Simplifying x = 83 + -0.5y
| 1.4+1.4z=7 | | 5(7x+4)=35x+20 | | 4x+5y-2=180 | | 4x+5y-12=180 | | 4x+5y-12=180 | | 10-6x=-3x-2 | | 3x+4-7x+10= | | -38+1.9y=1.9 | | -(3x-4)-(5x-4)+7=-5(x-5)-(8x+8)+6 | | 8x-2=74 | | 4q-(7q+13)=8-(11q-4) | | x+20+x+10+x=180 | | 27-6m=m^2 | | 7x-36-6x+12= | | x+2y-1=180 | | 19x-(7x-9)=45 | | 50y-42=45y+60 | | 7.5=1.5x+45 | | 24x-5-16x+2=18x-9-10x+15 | | (x-4)(x+4)(2x+11)=0 | | 2y+4(y-6)=8y-4(y-10) | | x=(5x+15)(6x-10) | | y=5x^2+13x+3 | | (x^2+6)+(2xi)=0 | | 3x+13-6x=18-15x+12x-5 | | 5r+-3r+2=5r-r | | (x-3)(x+1)(x-4-2i)(x-4+2i)=0 | | 7(x-9)+4=7x+7 | | x=(6x-10)(6x+10) | | 3x-45=56 | | 8+5x=7x+8 | | -3(-4p+5)=5(6p+15) |